IN VITRO DEGRADATION AND PHASE COMPOSITION OF COSMETIC EMULSIONS - CHELCEA, Ramona Ioana; (CORPODEAN) MOLDOVAN, Dumitriţa; DEMCO, Dan Eugen; CULEA, Eugen; FECHETE, Radu (Studia Universitatis Babeș-Bolyai Chemia, 2017)
Microscopic properties like network dynamics and phase compositions were studied for a series of commercially available cosmetics emulsions like hair shampoo, anti-UV shielding creams and hand and body creams. Proton longitudinal and transverse nuclear magnetic relaxations were measured by recording the 1D CPMG and 2D saturation recovery–CPMG echoes decays. The one and bi-dimensional inverse Laplace transformations reveals subtitle features which characterize the microscopic dynamic behaviour associated with the in vitro natural degradation of cosmetics. The IR and UV–VIS spectra were recorded and correlated with the NMR measurement.